Thermal insulation rubber mortar and preparation method thereof

CN122627747BActive Publication Date: 2026-10-30GUANGDONG UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611081480.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-30
Estimated Expiration
2046-07-21

AI Technical Summary

Technical Problem

[0004](一)解决的技术问题:本发明提供了一种保温隔热橡胶砂浆及其制备方法,解决了橡胶水泥砂浆保温性能和力学性能不佳的问题

Benefits of technology

[0021]本发明的巯基羧甲基纤维素微球含有大量的羧基,并修饰在橡胶粉表面,羧基可以与水泥硅酸盐的金属离子形成离子键、络合配位等作用,二者界面粘结力增强,可以提高橡胶粉与水泥砂浆之间的相容性,使橡胶粉与水泥形成连续密实的整体,避免加入橡胶粉而影响水泥砂浆的力学性能,从而保持很好的抗压强度和抗折强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122627747B_ABST
    Figure CN122627747B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of cement mortar, and discloses a heat-insulating rubber mortar and a preparation method thereof. Cement, sand, fly ash and modified rubber powder are dry-mixed in a stirrer, then water and a water reducing agent are added, and mixing and uniform mixing are carried out to obtain the heat-insulating rubber mortar. Mercapto carboxymethyl cellulose microspheres and rubber powder with low thermal conductivity form a double-layer thermal resistance composite phase, which significantly reduces the thermal conductivity of the cement mortar and is beneficial to improving the heat-insulating performance. The cellulose microspheres contain a large number of carboxyl groups and are modified on the surface of the rubber powder. The carboxyl groups can form ionic bonds, complex coordination and other actions with metal ions of cement silicates, the interface bonding force between the two is enhanced, the compatibility between the rubber powder and the cement mortar can be improved, the rubber powder and the cement form a continuous and dense whole, the mechanical performance of the cement mortar is not affected by the addition of the rubber powder, and thus the compressive strength and the bending strength are maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement mortar technology, specifically to a thermal insulation rubber mortar and its preparation method. Background Technology

[0002] Cement mortar is widely used in building walls, decorative tiling, basement waterproofing and damp-proofing, municipal and outdoor engineering, etc. Waste tire rubber itself has poor thermal conductivity and a microporous structure, which can trap static air and reduce air heat convection. When added to cement mortar, it can reduce its thermal conductivity, thus providing good thermal insulation performance. However, the interfacial properties between tire rubber and cement are poor, and the compatibility is not good. Furthermore, excessive addition of rubber, while improving thermal insulation performance, will seriously affect the mechanical strength of cement mortar.

[0003] Surface modification of tire rubber materials to improve their interfacial bonding performance with cement mortar is a research hotspot. Patent application CN117511021A discloses a simple method for preparing modified waste tire rubber, the finished product, and its application in cement mortar. Waste tire rubber is added to a tannic acid aqueous solution, titanium dioxide is added, and a reaction is carried out to obtain modified waste tire rubber. This effectively improves the mechanical properties and photocatalytic performance of the modified rubber composite cementitious material. However, this patent application does not significantly improve the thermal insulation performance of cement mortar. Summary of the Invention

[0004] (I) Technical problem solved: The present invention provides a thermal insulation rubber mortar and its preparation method, which solves the problem of poor thermal insulation performance and mechanical properties of rubber cement mortar.

[0005] (II) The technical solution of the present invention is: a thermal insulation rubber mortar, which, by mass parts, includes 30-34 parts cement, 100 parts sand, 2-5 parts fly ash, 2-5 parts modified rubber powder, 0.26-0.34 parts water-reducing agent, and 14-16 parts water.

[0006] The preparation method of thermal insulation rubber mortar is as follows: (1) Add carboxymethyl cellulose to 2-(N-morpholine) ethanesulfonic acid MES buffer solution, stir, add mercaptoethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and react. Dialyze the solution in a dialysis bag with distilled water and freeze dry to obtain mercaptomethyl carboxymethyl cellulose.

[0007] (2) Add mercapto-carboxymethyl cellulose to water, stir and mix to obtain an aqueous phase; add Span 80 to paraffin, stir and add the aqueous phase dropwise to emulsify, let stand and separate into layers, collect the lower aqueous phase, filter, wash the solid with water and ethanol, dry, and obtain mercapto-carboxymethyl cellulose microspheres.

[0008] (3) Add waste tire rubber powder to Tris-hydrochloric acid buffer solution, stir and add dopamine hydrochloride to react, then add mercaptocarboxymethyl cellulose microspheres to continue the reaction, filter and wash the solid with water and ethanol, dry to obtain modified rubber powder.

[0009] (4) Add cement, sand, fly ash and modified rubber powder to the mixer and dry mix. Then add water and water-reducing agent, mix well and obtain thermal insulation rubber mortar.

[0010] Furthermore, in (1), by mass fraction, the amount of carboxymethyl cellulose is 100 parts, mercaptoethylamine is 3-8 parts, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 7.8-20.5 parts, and N-hydroxysuccinimide is 4.6-12.5 parts.

[0011] Furthermore, the reaction in (1) is stirred at 20-30°C for 18-24 hours.

[0012] Furthermore, in (2), the volume ratio of water to paraffin is 1:(3.5-4.5).

[0013] Furthermore, in (2), the emulsification is carried out by stirring at 20-30°C for 5-7 hours.

[0014] Furthermore, in (3), by mass fraction, the amount of waste tire rubber powder is 100 parts, dopamine hydrochloride is 4-10 parts, and mercaptocarboxymethyl cellulose microspheres are 10-30 parts.

[0015] Furthermore, in (3), the reaction is carried out by stirring at 20-30℃ for 18-24h.

[0016] Furthermore, in (3), the reaction continues at 40-60℃ for 12-18h.

[0017] Furthermore, the dry mixing time in (4) is 1-2 min.

[0018] Furthermore, the mixing time in (4) is 2-3 minutes.

[0019] (III) Beneficial Technical Effects: This invention utilizes the amidation reaction between the amino group of mercaptoethylamine and some of the carboxyl groups of carboxymethyl cellulose to obtain mercaptomethyl carboxymethyl cellulose. Then, mercaptomethyl carboxymethyl cellulose microspheres containing porous and pore structures are prepared by a reverse-phase suspension method. Dopamine hydrochloride is used to form an adhesive polydopamine on the surface of rubber powder. Then, the quinone double bond of polydopamine undergoes an addition reaction with the mercapto groups of the mercaptomethyl carboxymethyl cellulose microspheres, thereby modifying the surface of the rubber powder with a layer of cellulose microspheres. Finally, it is mixed with cement, sand, etc., to obtain a thermal insulation rubber mortar.

[0020] The mercaptocarboxymethyl cellulose microspheres of the present invention contain a large number of pores and hollow structures, which can restrict the movement and convection of air molecules, reduce the thermal conductivity of air, and form a double-layer thermal resistance composite phase with rubber powder with low thermal conductivity. Adding a small amount of rubber powder can significantly reduce the thermal conductivity of cement mortar, which is beneficial to improving the thermal insulation performance.

[0021] The mercaptocarboxymethyl cellulose microspheres of the present invention contain a large number of carboxyl groups, which are modified on the surface of rubber powder. The carboxyl groups can form ionic bonds and complex coordination with the metal ions of cement silicate, thereby enhancing the interfacial adhesion between the two and improving the compatibility between rubber powder and cement mortar. This allows the rubber powder and cement to form a continuous and dense whole, avoiding the impact of adding rubber powder on the mechanical properties of cement mortar, and thus maintaining good compressive strength and flexural strength. Attached Figure Description

[0022] Figure 1 This is a scanning electron microscope image of mercaptocarboxymethyl cellulose microspheres. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0024] The following carboxymethyl cellulose is model CMCNA, manufactured by Guangzhou Anbi Chemical Technology Co., Ltd. The waste tire rubber powder has a particle size of approximately 20 mesh. The cement is PO42.5 cement. The sand is river sand with a fineness modulus of 2.41. The water-reducing agent is polycarboxylate superplasticizer, model MT-2800, manufactured by Guangzhou Moke Building Materials Technology Co., Ltd.

[0025] Example 1: (1) 18g of carboxymethyl cellulose was added to 700mL of 2-(N-morpholine) ethanesulfonic acid MES buffer solution. After stirring, 0.9g of mercaptoethylamine, 2.4g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.4g of N-hydroxysuccinimide were added. The mixture was stirred at 30℃ for 18h. The solution was dialyzed with distilled water in a dialysis bag and then freeze-dried to obtain mercaptomethyl carboxymethyl cellulose.

[0026] (2) Add 18g of mercapto-carboxymethyl cellulose to 350mL of water, stir and mix to obtain an aqueous phase; add 25g of Span 80 to 1.4L of paraffin, stir and then add the aqueous phase dropwise, stir and emulsify at 20℃ for 7h, let stand to separate the layers, collect the lower aqueous phase, filter, wash the solid with water and ethanol, dry, and obtain mercapto-carboxymethyl cellulose microspheres. Figure 1 Scanning electron microscopy images show that the mercaptocarboxymethyl cellulose microspheres have a uniform spherical structure and a porous surface.

[0027] (3) Add 180g of waste tire rubber powder to 3L Tris-hydrochloric acid buffer solution, stir, add 7.2g of dopamine hydrochloride, stir and react at 25℃ for 18h, then add 18g of mercaptocarboxymethyl cellulose microspheres, heat to 40℃, stir and react for 18h, filter, wash the solid with water and ethanol, dry, and obtain modified rubber powder.

[0028] (4) Add 3.2kg cement, 10kg sand, 0.3kg fly ash and 0.2kg modified rubber powder to the mixer and dry mix for 1 minute. Then add 1.5L water and 26g polycarboxylate superplasticizer and mix for 3 minutes to obtain thermal insulation rubber mortar.

[0029] Example 2: (1) 60g of carboxymethyl cellulose was added to 2.2L of 2-(N-morpholine) ethanesulfonic acid MES buffer solution. After stirring, 4.8g of mercaptoethylamine, 12.3g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 7.5g of N-hydroxysuccinimide were added. The mixture was stirred at 20°C for 24h. The solution was dialyzed with distilled water in a dialysis bag and then freeze-dried to obtain mercapto-modified carboxymethyl cellulose.

[0030] (2) Add 60g of mercaptocarboxymethyl cellulose to 1.2L of water, stir and mix to obtain an aqueous phase; add 92g of Span 80 to 5.4L of paraffin, stir and then add the aqueous phase dropwise, stir and emulsify at 30℃ for 5h, let stand to separate into layers, collect the lower aqueous phase, filter, wash the solid with water and ethanol, dry, and obtain mercaptocarboxymethyl cellulose microspheres.

[0031] (3) Add 300g of waste tire rubber powder to 3.8L Tris-hydrochloric acid buffer solution, stir, add 19.6g of dopamine hydrochloride, stir and react at 20℃ for 24h, then add 60g of mercaptocarboxymethyl cellulose microspheres, heat to 60℃, stir and react for 12h, filter, wash the solid with water and ethanol, dry, and obtain modified rubber powder.

[0032] (4) Add 3kg cement, 10kg sand, 0.5kg fly ash and 0.35kg modified rubber powder to the mixer and dry mix for 2 minutes. Then add 1.6L water and 34g polycarboxylate superplasticizer and mix for 2 minutes to obtain thermal insulation rubber mortar.

[0033] Example 3: (1) 120g of carboxymethyl cellulose was added to 7L of 2-(N-morpholine) ethanesulfonic acid MES buffer solution. After stirring, 3.6g of mercaptoethylamine, 9.4g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 5.6g of N-hydroxysuccinimide were added. The mixture was stirred at 20°C for 24h. The solution was dialyzed with distilled water in a dialysis bag and then freeze-dried to obtain mercapto-modified carboxymethyl cellulose.

[0034] (2) Add 120g of mercaptocarboxymethyl cellulose to 2.6L of water, stir and mix to obtain an aqueous phase; add 180g of Span 80 to 9.1L of paraffin, stir and then add the aqueous phase dropwise, stir and emulsify at 20℃ for 7h, let stand to separate into layers, collect the lower aqueous phase, filter, wash the solid with water and ethanol, dry, and obtain mercaptocarboxymethyl cellulose microspheres.

[0035] (3) Add 400g of waste tire rubber powder to 4.5L Tris-hydrochloric acid buffer solution, stir, add 40g of dopamine hydrochloride, stir and react at 30℃ for 18h, then add 120g of mercaptocarboxymethyl cellulose microspheres, heat to 60℃, stir and react for 12h, filter, wash the solid with water and ethanol, dry, and obtain modified rubber powder.

[0036] (4) Add 3.4kg cement, 10kg sand, 2kg fly ash and 0.5kg modified rubber powder to the mixer and dry mix for 1 minute. Then add 1.4L water and 32g polycarboxylate superplasticizer and mix for 3 minutes to obtain thermal insulation rubber mortar.

[0037] Comparative Example 1 differs from Example 1 in that waste tire rubber powder is used instead of modified rubber powder.

[0038] (1) Add 3.2kg cement, 10kg sand, 0.3kg fly ash and 0.2kg waste tire rubber powder to the mixer and dry mix for 1 minute. Then add 1.5L water and 26g polycarboxylate superplasticizer and mix for 3 minutes to obtain rubber mortar.

[0039] Comparative Example 2 differs from Example 1 in that it does not contain thiol carboxymethyl cellulose microspheres.

[0040] (1) Add 180g of waste tire rubber powder to 3L Tris-hydrochloric acid buffer solution, stir and then add 7.2g of dopamine hydrochloride. Stir and react at 25℃ for 18h. After filtration, wash the solid with water and ethanol and dry to obtain modified rubber powder.

[0041] (2) Add 3.2kg cement, 10kg sand, 0.3kg fly ash and 0.2kg modified rubber powder to the mixer and dry mix for 1 minute. Then add 1.5L water and 26g polycarboxylate superplasticizer and mix for 3 minutes to obtain thermal insulation rubber mortar.

[0042] Comparative Example 3: The main difference from Example 1 is that dopamine hydrochloride was not added.

[0043] (1) Add 180g of waste tire rubber powder to 3L of water, stir, add 18g of mercaptocarboxymethyl cellulose microspheres, heat to 40℃, stir for 18h. The surface of the rubber powder does not contain polydopamine and cannot react with mercaptocarboxymethyl cellulose microspheres. After filtration, wash the solid with water and ethanol, and dry to obtain a blend of cellulose microspheres and rubber powder.

[0044] (2) Add 3.2kg cement, 10kg sand, 0.3kg fly ash and 0.2kg modified rubber powder to the mixer and dry mix for 1 minute. Then add 1.5L water and 26g polycarboxylate superplasticizer and mix for 3 minutes to obtain thermal insulation rubber mortar.

[0045] Comparative Example 4: The difference from Example 1 is that carboxymethyl cellulose microspheres were used instead of thiol carboxymethyl cellulose microspheres.

[0046] (1) Add 18g of carboxymethyl cellulose to 350mL of water, stir and mix to obtain an aqueous phase; add 25g of Span 80 to 1.4L of paraffin, stir and then add the aqueous phase dropwise, stir and emulsify at 20℃ for 7h, let stand to separate into layers, collect the lower aqueous phase, filter, wash the solid with water and ethanol, dry, and obtain carboxymethyl cellulose microspheres.

[0047] (2) Add 180g of waste tire rubber powder to 3L Tris-hydrochloric acid buffer solution, stir and then add 7.2g of dopamine hydrochloride. Stir and react at 25℃ for 18h. Then add 18g of carboxymethyl cellulose microspheres, heat to 40℃ and stir for 18h. Carboxymethyl cellulose microspheres do not contain thiol groups and cannot react with polydopamine on the surface of rubber powder. After filtration, wash the solid with water and ethanol, and dry to obtain cellulose microsphere-rubber powder blend.

[0048] (3) Add 3.2kg cement, 10kg sand, 0.3kg fly ash and 0.2kg cellulose microsphere-rubber powder blend to the mixer and dry mix for 1 minute. Then add 1.5L water and 26g polycarboxylate superplasticizer and mix for 3 minutes to obtain rubber mortar.

[0049] Vibrate the rubber mortar on a vibrating table for 3 minutes, pour it into a mold, and cure it according to the method of GB / T 17671-2021 for 28 days. Then test the mechanical properties of the molded sample.

[0050] The thermal conductivity of the rubber mortar curing specimen was tested according to the method of GB / T 10297-2015.

[0051] Table 1 Performance Tests

[0052] As shown in Table 1, Example 1 utilizes dopamine to generate a highly adhesive polydopamine layer on the surface of rubber powder. Then, the quinone double bonds of polydopamine undergo an addition reaction with the thiol groups of mercaptocarboxymethyl cellulose microspheres, thereby modifying the surface of the rubber powder with a layer of cellulose microspheres. These cellulose microspheres contain numerous pores and hollow structures, which can restrict the movement and convection of air molecules, reducing air thermal conductivity. They form a double-layer thermally resistive composite phase with the low thermal conductivity of the rubber powder, significantly reducing the thermal conductivity of the cement mortar, which is significantly lower than that of Comparative Example 1, thus improving thermal insulation performance. Furthermore, the mercaptocarboxymethyl cellulose microspheres contain a large number of carboxyl groups, which, when modified on the surface of the rubber powder, can form ionic bonds and complex with the metal ions of cement silicate, enhancing the interfacial adhesion between the two. This improves the compatibility between the rubber powder and the cement mortar, allowing the rubber powder and cement to form a continuous and dense whole, avoiding the impact of adding rubber powder on the mechanical properties of the cement mortar, thus maintaining excellent compressive and flexural strength, significantly higher than that of Comparative Example 1. In Examples 2 and 3, different proportions of cement, sand, and modified rubber powder were adjusted to obtain cement mortars that also had high mechanical strength and low thermal conductivity.

[0053] Comparative Example 2 did not contain mercaptocarboxymethyl cellulose microspheres, and the thermal conductivity of the cement mortar was greater than that of Example 1. Although the rubber powder was modified with polydopamine, it did not contain carboxyl groups, resulting in lower interfacial adhesion between the rubber powder and cement. Consequently, the compressive strength and flexural strength of the cement mortar were lower than those of Example 1.

[0054] In Comparative Example 3, no dopamine hydrochloride was added, so the rubber powder could not react with the mercaptocarboxymethyl cellulose microspheres. When the resulting cellulose microsphere-rubber powder blend was mixed with cement, the cellulose microspheres easily separated from the rubber powder, failing to form a double-layer thermally resistant composite phase and failing to improve the compatibility between the rubber powder and the cement mortar. As a result, the thermal conductivity of the cement mortar was higher than that of Example 1, and the mechanical strength was lower than that of Example 1.

[0055] The carboxymethyl cellulose microspheres in Comparative Example 4 do not contain thiol groups and cannot react with the polydopamine on the surface of the rubber powder. When the resulting cellulose microsphere-rubber powder blend is mixed with cement, the cellulose microspheres easily separate from the rubber powder, failing to form a double-layer thermally resistant composite phase and failing to significantly improve the compatibility between the rubber powder and the cement mortar. This results in the cement mortar having a higher thermal conductivity and lower mechanical strength than that of Example 1.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A thermal insulation rubber mortar, characterized in that, The thermal insulation rubber mortar, by weight, comprises 30-34 parts cement, 100 parts sand, 2-5 parts fly ash, 2-5 parts modified rubber powder, 0.26-0.34 parts water-reducing agent, and 14-16 parts water; The modified rubber powder is prepared according to the following method: (1) Add carboxymethyl cellulose to 2-(N-morpholine) ethanesulfonic acid buffer solution, stir, add mercaptoethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, react, dialyze the solution with distilled water in a dialysis bag, freeze dry to obtain mercaptomethyl carboxymethyl cellulose; (2) Add mercapto-carboxymethyl cellulose to water, stir and mix to obtain an aqueous phase; add Span 80 to paraffin, stir and then add the aqueous phase dropwise to emulsify, let stand and separate into layers, collect the lower aqueous phase, filter, wash the solids, and dry to obtain mercapto-carboxymethyl cellulose microspheres. (3) Add waste tire rubber powder to Tris-hydrochloric acid buffer solution, stir and add dopamine hydrochloride to react, then add mercaptocarboxymethyl cellulose microspheres to continue the reaction, filter and wash the solid, dry to obtain modified rubber powder; In (2), the volume ratio of water to paraffin is 1:(3.5-4.5). In step (2), the emulsification is carried out by stirring at 20-30°C for 5-7 hours.

2. The thermal insulation rubber mortar according to claim 1, characterized in that, In (1), by mass fraction, the amount of carboxymethyl cellulose is 100 parts, mercaptoethylamine is 3-8 parts, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 7.8-20.5 parts, and N-hydroxysuccinimide is 4.6-12.5 parts.

3. The thermal insulation rubber mortar according to claim 1, characterized in that, The reaction in (1) is stirred at 20-30℃ for 18-24h.

4. The thermal insulation rubber mortar according to claim 1, characterized in that, In step (3), by mass, the amount of waste tire rubber powder is 100 parts, dopamine hydrochloride is 4-10 parts, and mercaptocarboxymethyl cellulose microspheres are 10-30 parts.

5. The thermal insulation rubber mortar according to claim 1, characterized in that, In step (3), the reaction is carried out by stirring at 20-30°C for 18-24 hours.

6. The thermal insulation rubber mortar according to claim 1, characterized in that, In step (3), the reaction continues at 40-60°C for 12-18 hours.

7. A method for preparing thermal insulation rubber mortar as described in any one of claims 1-6, characterized in that, The preparation method is as follows: cement, sand, fly ash, and modified rubber powder are added to a mixer and dry-mixed. Then water and water-reducing agent are added and mixed evenly to obtain thermal insulation rubber mortar.

8. The method for preparing thermal insulation rubber mortar according to claim 7, characterized in that, The dry mixing time is 1-2 minutes, and the mixing time is 2-3 minutes.

Citation Information

Patent Citations

  • Simple preparation method of modified waste tire rubber, finished product and application of modified waste tire rubber in cement mortar

    CN117511021A

  • Multi-source waste residue-based 3D concrete printing material and preparation method therefor

    WO2023124471A1

  • Rubber filler, rubber composite material containing same, preparation method therefor, and use thereof

    WO2024255096A1